The mediating role of optimism between reading habits and meaningful living - Guven, Ahmet Zeki; Banaz, Emrullah; Özbilen, Uğur; Şahin, Tuğrul Gökmen (Frontiers in Psychology, 2025)
The present study sought to examine the relations between reading habits, perceived meaningful living, and optimism through structural equation modeling. To this end, we recruited undergraduate students enrolled in the Turkish language teaching program of a state university and collected the data using the Reading Attitude and Habits Scale, the Meaningful Living Scale and the Optimism-Pessimism Questionnaire. More than half (58.4%) of students were females, 52% were aged 21–30 years, and 34.2% were second-year students. The data were analyzed using SPSS 24.0 and SPSS AMOS 20.0. The findings showed a significant relationship between reading habits and meaningful living, with optimism serving as a significant mediator. Model fit indices confirmed the validity of the SEM model (RMSEA = 0.061, CFI = 0.94, TLI = 0.96). We also found that optimism served as a significant mediator in the relation between reading habits and perceived meaningful living. The findings suggest encouraging undergraduate students’ reading habits and designing and offering counseling services to foster students’ optimism and perceived meaningful living. Moreover, further research with diverse demographic groups is needed to elucidate more on the subject.